Peningkatan Hasil Belajar Pendidikan Pancasila Menggunakan Model Problem Based Learning (PBL) Dengan Media Quizziz Paper Mode pada Siswa Kelas V A Di SDN 004 Samarinda Ilir - Irda Lola; Tri Wahyuningsih; Khusnul Khotimah; Andi Asrafiani Arafah (Mataram University, 2026)
This study aims to improve the learning outcomes of Pancasila Education through the application of the Problem Based Learning model with Quizziz Paper Mode media in class V-A background of this study is the low learning outcomes of students who have not reached the Learning Objectives Achievement Criteria (KKTP) due to the lack of variety of learning models and media used by teachers. This study uses the Classroom Action Research (CAR) method which is carried out for two cycles and each cycle consists of two meetings. The research procedure consists of four stages, namely the planning stage, the action implementation stage, the observation stage, and the reflection stage. The subjects in this study were 28 class V-A students of SDN 004 Samarinda Ilir and the object of this study was the learning outcomes of Pancasila Education on the material of Cultural and Social Diversity in Indonesia using the Problem Based Learning model with Quizziz Paper Mode media. Data collection techniques used were observation of teacher and student activities and learning outcome tests. The data analysis technique in this study uses the percentage of teacher and student activities, completeness of learning outcomes, average, final grades, and improvement in student learning outcomes. Based on the research, it can be concluded that there has been an improvement in Pancasila Education learning outcomes on Cultural and Social Diversity in Indonesia using the Problem Based Learning model with Quizziz Paper Mode for grades V-A at SDN 004 Samarinda Ilir. This improvement in student learning outcomes is evidenced by the average Pancasila Education score in the pre-cycle of 56.07, with a completion rate of 28.57%. This then increased to 71.96 in the first cycle, with a 25% increase in learning outcomes and a completion rate of 53.57%. In the second cycle, the average score increased to 85.35, an increase from the pre-cycle score of 57.14% and a completion rate of 85.71%.